Biologics in orthopaedic surgery - Stannard, James P.; Cook, James L. (James Lee) 1965-; Fortier, Lisa Ann 1965- (Thieme, 2016)
Biologics in Orthopaedic Surgery is a clinical reference that provides readers with a thorough review of state-of-the-art orthobiologics currently used by orthopaedic surgeons, including cutting edge developments in this field. Chapters are written by world-renowned experts and cover the relevant science, regulatory aspects, and practical application recommendations for orthobiologics.